A multi-constrained multicast QoS routing algorithm - Feng, Gang (Computer communications, 2006)
Opposed to the situation that the constrained minimum Steiner tree (CMST) problem has been attracting much attention in quality of service (QoS) routing area, little work has been done on multicast routing subject to multiple additive constraints even though this is required by many emerging applications. In this paper, we propose a heuristic HMCMC to find feasible solutions to this problem. HMCMC has a provably low time complexity, and its basic idea is to construct a multicast tree step-by-step, which is done essentially based on the latest research results on multi-constrained unicast routing. Computer simulations demonstrate that HMCMC can achieve a high success ratio of finding feasible solutions.